Regulasi Emosi pada Mahasiswa dengan Ciri Kepribadian Perfeksionis - Badratun Nafis; Sri Nurhayati Selian (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This research is motivated by the phenomenon of high academic pressure among students who possess excessively high self-standards or perfectionistic personality traits. The primary issue examined is how these students manage their emotions amidst a constant fear of failure. This study aims to gain a profound understanding of the emotion regulation strategies employed by perfectionistic students. The research method used is qualitative with a phenomenological approach to explore the participants 3 subjective experiences. Data were collected through in-depth interviews with active students selected via purposive sampling. The results indicate that participants tend to use maladaptive strategies, such as expressive suppression and procrastination, when they feel unable to achieve maximum targets. Social support and emotional maturity were identified as key factors helping them transition toward adaptive strategies. The study concludes with an emphasis on the necessity of specialized psychological support for perfectionistic students to develop self-compassion.